Peran Facebook Marketplace dan Financing Convenience Terhadap Daya Beli Konsumen di Erafone Rembiga - I Gede Bagus Swardana; Dewi Kusumasanthi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the role of social media, particularly Facebook Marketplace, and financing convenience in influencing consumer purchasing power at Erafone Rembiga in the sales of gadgets and accessories. With the development of technology, consumer behavior in making transactions has shifted from conventional to fully digital, impacting adjustments in marketing techniques. The use of social media has become a driving force in reaching more consumers through promotions that have been carried out. Therefore, the study focuses on the effectiveness of Facebook Marketplace in increasing consumer purchase interest and the role of financing convenience in boosting consumer purchasing power. This study uses a qualitative method with an interview observation approach and participatory observation, thereby obtaining research results that show that Facebook Marketplace plays an important role in attracting consumer attention and interest through easy access to information, appealing product displays, and responsive communication. In addition, financing convenience, in the form of installment or credit services through various financing application platforms, has proven to be a key factor in enhancing purchasing decisions, especially for high-priced products. Easy requirements, flexible terms, and low-interest promotions up to 0% encourage consumers to make purchases. Therefore, these two factors are proven to be interrelated and contribute significantly to increasing consumer purchasing power at Erafone Rembiga.